A perfect storm: How tumor biology, genomics, and health care delivery patterns collide to create a racial survival disparity in breast cancer and proposed interventions for change. (9th April 2015) - Daly, Bobby; Olopade, Olufunmilayo I.
<x xml:space="preserve">Abstract</x> It is well known that there is a significant racial divide in breast cancer incidence and mortality rates. African American women are less likely to be diagnosed with breast cancer than white women but are more likely to die from it. This review explores the factors that may contribute to the racial survival disparity. Consideration is paid to what is known about the role of differences in tumor biology, genomics, cancer screening, and quality of cancer care. It is argued that it is the collision of 2 forces, tumor biology and genomics, with patterns of care that leads to the breast cancer mortality gap. The delays, misuse, and underuse of treatment for African American patients are of increased significance when these patients are presenting with more aggressive forms of breast cancer. In the current climate of health care reform ushered in by the Affordable Care Act, this article also evaluates interventions to close the disparity gap. Prior interventions have been too narrowly focused on the patient rather than addressing the system and improving care across the continuum of breast cancer evaluation and treatment. Lastly, areas of future investigation and policy initiatives aimed at reducing the racial survival disparity in breast cancer are discussed. CA Cancer J Clin 2015;65: 221–238. © 2015 American Cancer Society.